Kepentingan Amerika Serikat menggeser arah kekuatan militer Ke Kawasan Pasifik. - Abdul Rasyid (HI 14 UMY 042, 2014)
The Asia-Pacific is a region that is growing into one of the world's economic center. Rapid economic growth makes many countries glance this region. No exception the United States, the last in 2011 the United States issued a policy on the presence of its military forces back in the region. Unmitigated strength reaches 60 percent of the total military force. The presence of the U.S. military gets a variety of reactions from the countries that are in this region. For its allies certainly open hand over the presence of the U.S. military, another case for the non-aligned countries that consider the U.S. military presence may interfere with the existence of each country. U.S. bilateral relations with the countries that have the same perception of China as a threat such as India, Vietnam, the Philippines and Singapore. The United States believes that the most successful alliance is a partnership in which the state becomes a horse and driving into the other country. Not two or more drivers without a horse to driving. U.S. military presence in the Asia Pacific region related of the interest economic, political, and defense and security. The United States wants the natural resources that are in the region to sustain its economy sector. Remain to maintain the hegemony of the world and part of the U.S. defense doctrine that carries global defense. United States requires of sea line of communications that extend from the South China Sea through the Strait of Malacca as ships traffic to stay safe from closure. Concerns the United States against the rise of China's military that allows China to make Anti Access / Anti Denial on the success of China's developing an Armed Anti-Ship Ballistic Missiles / Dong Feng 21D. Keywords: Shifting the military power of the United States, Asia Pacific, the interest of political economy.